Przestrzenna i czasowa zmienność rodzajów chmur nad Polską w latach 1996-2020 - Grajek, Zofia; Dyszy, Wiktoria (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The subject of the study is a comprehensive qualitative and quantitative analysis of the type of cloud cover over Poland in 1996–2020. The analysis was based on the characteristics of particular types of clouds at three levels, based on hourly measurement data from 36 meteorological stations (IMWM-NRI). The variability of the share of cloud types was analysed on three levels in the multi-annual, annual and daily course. Maps of spatial distribution for selected clouds were plotted. In the study of the multi-year period, clouds of the low-level were observed most frequently, and the most numerous cloud type was Stratocumulus. Altocumulus clouds were found to have the highest frequency on the mid-level, while Cirrus clouds of various species were found on the high-level. On the low-level, the highest increase in the share in the analysed multi-year period was recorded for Stratocumulus clouds, and the highest decrease for moderately and strongly uplifted Cumulus clouds. On the mid-level, the largest increase in the share was observed for Altocumulus clouds, and the largest decrease for Nimbostratus clouds. Among the clouds of the high-level, the greatest increase in the proportion of Cirrostratus clouds not stretching the sky was observed, while the greatest decrease in the share was for the Cirrus uncinus clouds. The annual and daily courses on all the levels showed cyclic occurrence, meaning that the different types of clouds have characteristic periods when they are observed more or less frequently, both on an annual and daily basis.